The insurance industry in Algeria: what is its role in economic development? - Hasnaoui Meriem; Hassani Hocine; Himrane Mohammed (Journal of North African Economies, 2025)
The cointegration test indicates the existence of a long-run relationship between insurance industry and economic growth. The study shows a negative effect of life insurance penetration on economic growth in the long and short terms, and the existence of a positive impact of non-life insurance penetration on economic growth. Therefore, the finding of this study does strongly support the view that economic growth enhances insurance industry in Algeria.